The metaphysical symbolism of the chinese tortoise - Chong, Alan Wei Lun (2018)
The objective of the thesis is two-fold: 1) to examine the metaphysical symbolism of the Chinese tortoise and establish the visual grammar of the tortoise symbolism. As the topic will be approached in a visual communication point of view, infographics such as diagrams will be illustrated to demonstrate how Chinese cosmogony and cosmology are reflected on the metaphysical symbolism of the tortoise. 2) To investigate the myriad layers of meanings embedded within the tortoise symbol. By doing so, we will attempt to foreground any obscured meanings and at the same time, enhance and deepen our understanding towards both the tortoise symbol and the methodology of analysis and answer the question towards the meaning of the entwined form of the tortoise and snake symbolism. The established scholars of Chinese philosophies such as Wing Tsit Chan and Feng Youlan tackle the discourse and tenets of Chinese philosophy, ethics and metaphysics, yet there remains a missing link of transition from the written to visuals. On the other hand, the Research Institute of Asian Design The Research Institute of Asian Design aims to rediscover vital formative arts in Asia, where rich and traditional cultures, which are different from Western culture, are still rooted in daily life, and to establish “Asian Design” based on its unique usage. Through research on such projects as “Asian headgear,” “Asian plants and trees,” “Asian spirals” as well as the already launched study on “Asian floats,” we will reaffirm the values and meaning of the vast number of formative arts embraced by Asian cultures to use them in modern art. Hence, the paper attempts to synthesize these classical thoughts with the modern above-mentioned methodology to demonstrate how visual language can be scaled to apply visually to a macrocosmic and to a microcosmic view at the same time. This demonstrates the flexibility and attempts to apply the vernacular of Chinese metaphysical tenets to contextual application. The paper analyzes the typologies of the tortoise in the Chinese cosmogonic myths and at the same time, introduce the Chinese cosmology namely their model of the cosmos, which includes the Yinyang thought, and the five elements theory to demonstrate the above-mentioned rationale. To further substantiate the research and expand the lateral scope, the paper will draw on different viewpoints and methodologies of scholars such as René Guénon and Mircea Eliade specializing in traditional symbolism and their macrocosmic view on symbolisms to aid in connecting these seemingly unrelated concepts from text to image. Hence, the images of the tortoise and the structure of the whole thesis will be classified into ‘typologies’ to reflect the cosmogonic pattern to further demonstrate this progression. From the undifferentiated ‘One’ or the primordial chaos, we will be introduced to the beginning of the universe as told in myths involving the tortoise. The next part of the process is the differentiating, which brings us to the ‘Two’ complementary force of Yin and Yang, namely Heaven and Earth and their symbolic shapes reflected on the form of the tortoise as well as the tortoise entwined with snake (black tortoise). The next part is the ‘Five’ elements generated by the interaction of the two which we will cover the black tortoise along with the three other important cardinal creatures in bronze mirrors, Feng Shui and select material cultures containing the four cardinal creatures. Finally, we will conclude with our immediate experiences of the tortoise in Singapore and in the contemporary under the ‘ten thousand things’ as it is considered the final stage of the cosmogonic process and where we are currently situated.